Electronic structure and optical properties of RbPb2Br5. (April 2016) - Lavrentyev, A.A.; Gabrelian, B.V.; Vu, V.T.; Denysyuk, N.M.; Shkumat, P.N.; Tarasova, A.Y.; Isaenko, L.I.; Khyzhun, O.Y.
Abstract: We report on density functional theory (DFT) calculations of the total and partial densities of states of rubidium dilead pentabromide, RbPb2 Br5, employing the augmented plane wave+local orbitals (APW+lo) method as incorporated in the WIEN2k package. The calculations indicate that the Pb 6s and Br 4p states are the dominant contributors to the valence band: their main contributions are found to occur at the bottom and at the top of the band, respectively. Our calculations reveal that the bottom of the conduction band is formed predominantly from contributions of the unoccupied Pb 6p states. Data of total DOS derived in the present DFT calculations are found to be in agreement with the experimental X-ray photoelectron valence-band spectrum of this compound. The predominant contributions of the Br 4p states at the top of the valence band of rubidium dilead pentabromide are confirmed by comparison on a common energy scale of the X-ray emission band representing the energy distribution of the valence Br p states and the X-ray photoelectron valence-band spectrum of the RbPb2 Br5 single crystal. Main optical characteristics of RbPb2 Br5, such as dispersion of the absorption coefficient, real and imaginary parts of dielectric function, electron energy-loss spectrum, refractive index, extinction coefficient and optical reflectivity are explored for RbPb2 Br5 by the DFT calculations. Graphical abstract: Highlights: DFT calculations of total and partial densities of states of RbPb2 Br5 are reported. Pb 6s and Br 4p states are the dominant contributors to the valence band. The conduction band is formed mainly from contributions of unoccupied Pb 6p states. Electronic structure of RbPb2 Br5 is studied by XPS and XES methods. Main optical characteristics of RbPb2 Br5 are calculated.